"Cold" Spondylodiscitis on 18F-FDG PET/CT in a Patient With Myelofibrosis. (March 2016) - Rousseau, Etienne; Keu, Khun Visith
Abstract : Abstract: A 74-year-old man was evaluated by bone scan for possible rib fractures, which revealed a diffuse skeletal uptake secondary to myelofibrosis and focal midthoracic uptake. Chest CT and 18 F-FDG PET/CT demonstrated pathological vertebral fractures of the midthoracic spine, which appeared as a cold defect on PET comparing to intense marrow uptake related to myelofibrosis and a lung nodule with a low uptake, later biopsy-proven as non–small cell lung carcinoma (NSCLC). MRI confirmed CT findings for the spine noting also an enhanced epidural collection. Biopsies did not reveal malignant cells. Final diagnosis was spondylodiscitis and a stage I NSCLC.